Kesenjangan Komunikasi Orang Tua dan Anak dalam Menghadapi Pembelajaran Online di Masa Pandemi Covid-19 - Intan Mustafa; Lodowik Nikodemus Kedoh; Maria Yosephine Desire (Jurnal Nomosleca, 2021)
Abstract: Learn from home has become a new trend today. This study examines how the communication gap that occurs between parents and children in the online learning process during the covid-19 pandemic. The method used is a case study, with data collection techniques through observation, interviews and documentation review. The results of the study indicate that quite a number of problems have arisen against this government policy, and one of them is the communication problem of parents in their unpreparedness having a dual role in their upbringing as teachers, motivators and facilitators for their children. In addition, other problems such as supporting facilities, social environment and children's mentality are other obstacles that contribute to creating a communication gap between parents and children. Through this research, it is hoped that the communication relationship between parents and children should be a priority, so that the current pandemic situation does not necessarily reduce children's interest in learning and academic potential. Keywords: Communication Gap, Online Learning, Covid-19 Pandemic